2021
DOI: 10.1093/deafed/enab029
|View full text |Cite|
|
Sign up to set email alerts
|

Joint Attention in the Context of Hearing Loss: A Meta-Analysis and Narrative Synthesis

Abstract: Joint attention is important for children’s language development. We report two meta-analyses that demonstrate that the congruency in hearing status between parent and child affects the establishment and maintenance of joint attention. Dyads consisting of hearing parents and children with hearing loss, achieve fewer and briefer moments of joint attention in comparison to dyads of hearing parents and hearing children and dyads of deaf parents and deaf children. The theoretical and practical implications of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For children who are responding to and developing sign language, and/or benefiting from lip patterns and facial expressions, a visual way of gaining attention may be more effective. Parents of deaf children make more frequent use of visual and tactile strategies to gain their child’s attention when compared to hearing parents of hearing children [ 38 ]. In this current e-Delphi, tactile strategies for gaining attention or using multiple modes of attention getting at one time did not reach consensus.…”
Section: Discussionmentioning
confidence: 99%
“…For children who are responding to and developing sign language, and/or benefiting from lip patterns and facial expressions, a visual way of gaining attention may be more effective. Parents of deaf children make more frequent use of visual and tactile strategies to gain their child’s attention when compared to hearing parents of hearing children [ 38 ]. In this current e-Delphi, tactile strategies for gaining attention or using multiple modes of attention getting at one time did not reach consensus.…”
Section: Discussionmentioning
confidence: 99%
“…DHH children of hearing parents have an overall poorer experience of two-way interaction, compared to their hearing peers. They are usually more interrupted during their communicative attempts (18), more requested to produce words rather than being engaged in conversation, and experience fewer and shorter moments of joint attention (19) and vocal turn-taking (20,21). This is because hearing parents of DHH children tend to be less responsive (4) and more directive in their interactions (22,23), compromising children's ability to maintain attention (23,24) and giving less feedback on their communicative attempts [see (1,25)].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review and meta‐analysis, parents’ linguistic input was found to be a substantive predictor of deaf children's expressive language and explained 31.7% of the variance in deaf children's language scores (Holzinger et al., 2020). Another recent systematic review of 26 studies from six countries uncovered the strategies used by hearing and deaf parents to gain their deaf children's attention, as well as the strong positive associations between the length of joint engagement between parent and child and child language scores (Lammertink et al., 2021). Other international studies have uncovered additional parental features in PCI associated with higher language scores for deaf children, such as higher skills in maternal responsiveness and non‐intrusiveness (Niparko et al., 2010), a higher number of conversational turns between the parent and child (Ambrose et al., 2014), a wider range of word types and language structures used by the parent (DesJardin & Eisenberg, 2007), as well as parents’ recasts and the use of open‐ended questions (Cruz et al., 2013).…”
Section: Introductionmentioning
confidence: 99%